Implementation and analysis of deflection switched reluctance generator for underwater flow generation applications. Issue 8 (1st July 2022) - Li, Zheng; Wang, Xueting; Wei, Xiaopeng; Liu, Libo; Gao, Menghai; Cheng, Liyuan; Liu, Mengjie; Liu, Huixian; Sun, Hexu
Abstract: This paper proposes a dual‐stator switched reluctance generator (DSSRG) which can be applied to underwater power generation. DSSRG is connected with the propeller. When the propeller deflects, it can drive the generator to deflect for underwater power generation and improve the conversion efficiency of the motor. Firstly, taking the underwater propeller as the research object, the pressure and torque characteristics of the propeller at different deflection angles are studied by using CFX software. Then, the structure of DSSRG is modelled and analysed, and the voltage and current characteristics of DSSRG at different speeds and deflection angles are analysed. Finally, an underwater generator prototype is established to verify the rationality of the underwater DSSRG and the feasibility and stability of the power generation system.